Bag it [videorecording (DVD)] - Berrier, Jeb; Beraza, Suzan; Beraza, Suzan (Docuramafilms, 2010)
Americans use 60,000 plastic bags every five minutes that we then throw away. But where is 'away?' Where do the bags and other plastics end up, and at what cost to our environment, marine life and human health? Follows 'everyman' Jeb Berrier as he navigates our plastic world. Jeb is not a radical environmentalist, but an average American who decides to take a closer look at our cultural love affair with plastics.